Atlas of clinical gross anatomy - Moses, Kenneth P. (Elsevier/Saunders, 2013)
Atlas of Clinical Gross Anatomy uses over 500 incredibly well-executed and superb dissection photos and illustrations to guide you through all the key structures you'll need to learn in your gross anatomy course. This medical textbook helps you master essential surface, gross, and radiologic anatomy concepts through high-quality photos, digital enhancements, and concise text introductions throughout.